Use of hypodermoclysis in the treatment of elderly people in institutional care - Klavdija Kobal Straus (Nurses and Midwives Association of Slovenia, 2014)
Introduction: Hypodermoclysis is a way of administering fluids to the body by using a subcutaneous infusion. Research shows that this procedure is as effective as the more established intravenous infusion, posing no serious complications. Method: For this study, a descriptive quantitative method was used. The data were gathered through a structured survey questionnaire specifically designed for the purpose of the study. It consisted of 14 questions. The questionnaire was completed and returned by 40 nursing care managers in the old people's homes. The questionnaire was designed and distributed by means of the 1ka web tool on February 10, 2013 and the answers were collected by February 26,  2013. The data analysis was performed using the software package 1ka, MS Office (Word, Excel) and SPSS 18.0. Results: With regard to geographical location of the old people's homes inSlovenia, the familiarity with and the use of hypodermoclysis does not vary substantially (χ2 = 0.440, p = 0.507). Complications related to this procedure of administering fluids are rare when it is administered in conformity with accepted indications and guidelines. The risks of hypodermoclysis are not directly related to the rate of administration (χ2 = 0.000, p = 1.000). The research did not establish any correlation between the frequency of complications and the education level of the nursing staff (χ2 = 3.900, p = 0.420). Discussion and conclusion: The research shows that hypodermoclysis is an established and widely used procedure among the professionals who took part in the research. As hypodermoclysis is a safe, easy and financially accessible way of administering fluids, suitable for use both in institutions as well as in home care, the time has come for resurrection and evaluation of this alternative infusion technique for widespread future use.